The fall of the â€œWhite Masksâ€ of Critical Criminology: theoretical approximations from Frantz Fanon - Tomaz de Souza, Luanna (2023)
This study has the objective of analyse the possible contributions of Frantz Fanon’s work to the critical criminology’s comprehension of racial questions. From an inductive analysis, it is emprehended a bibliographical research of qualitative character. Firstly it is dealt with the critical criminology, both with the purpose to delimit the studied field and to analyse the critics about its insufficieny in the aprehension of racial matters. Posteriorly, it is introduced the studied author, by his theoretical contribution, mainly from some of its main readers. Lastly, possibilities of aprehension of Frantz Fanon’s work by the critical criminology are analyzed. Concluded that, besides the few approaches of the fanonian work in the juridic field, it has a great importance to the studies about racism, which advances offer various ways to deepening of the critical criminology.